A Case of Successful Treatment of Left Ventricular Rupture after Transcatheter Aortic Valve Implantation - Tuleutayev, Rustem; Abzaliyev, Kuat; Kolesnikov, Alexey; Kim, Igor; Abzaliyeva, Symbat (Acta medica Lituanica, 2024)
Background: The article talks about a patient who had nonrheumatic disease of the aortic valve and had a left ventricular rupture during a transcatheter aortic valve implantation (TAVI) procedure. Methods: The discrepancy between the size of the prosthesis and the size of the native aortic valve (mismatch) led to the need to deploy a second prosthesis, which was dislocated into the left ventricular cavity and led to myocardial damage and the development of tamponade. Results: As a result of timely cardiac surgery and effective measures of the emergency support service, both prostheses were removed from the left ventricular cavity, the aortic valve was replaced with a “Medtronic Hankock No. 25” biological prosthesis, and the left ventricular myocardial rupture was sutured. Conclusions: In case of the development of such complications during the transcatheter aortic valve implantation (TAVI) procedure with asystole and cardiac tamponade, it was suggested to conduct cardioplegia (instead of chest compressions).